Congenital Double Pylorus - Ruvashni Naidoo; Bhugwan Singh (Case Reports in Gastrointestinal Medicine)
The double pylorus is an uncommon finding and maybe congenital due to gastrointestinal duplication abnormality or more commonly secondary to peptic ulcer disease. The case we present is an elderly patient with mild dyspeptic symptoms who had an upper endoscopy as part of her investigative workup. The congenital double pylorus, being asymptomatic, may often go undetected. It is sometimes found incidentally on upper endoscopy, but needs no directed therapy. It is not associated with any specific complication.